Response of Aerobic Anoxygenic Phototrophic bacteria to carbon limitation - Kasia Piwosz (PANGAEA, 2024)
Aerobic Anoxygenic Phototrophic (AAP) bacteria are an important component of freshwater bacterioplankton. They can support their heterotrophic metabolism with energy from light, and by that enhance their growth efficiency. Based on results from cultures, it was hypothesized that photoheterotrophy provides an advantage under carbon limitation and facilitates access to recalcitrant or low-energy carbon sources. However, verification of these hypotheses for natural AAP communities has been lacking. Here, we conducted whole community manipulation experiments and compared the growth of AAP bacteria under carbon limited and with recalcitrant (lignin) or low energy (acetate) carbon sources under dark and infra-red (IR) light conditions to elucidate how they profit from photoheterotrophy. We performed two whole community manipulation experiments in 2-litre microcosms. The first experiment was conducted in June 2018. Lignin was used as the recalcitrant carbon source. Samples were collected every 12 hours. The second experiment was conducted in October 2018. Acetate was used as the low-energy carbon source. Samples were collected every 24 hours. Both experiments were done in at in situ temperature. We measured concentrations of bacteriochlorophyll-a, total prokaryotic count, aerobic anoxygenic phototrophic bacteria count, and heterotrophic nanoflagellates count. This dataset is related to Piwosz et al. (in prep).